2013
DOI: 10.1177/0957650913487530
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study on the inlet nozzle of a small squirrel-cage fan

Abstract: The squirrel-cage fan performance is sensitive to the inlet nozzle configuration. In this paper, an experimental study combined with numerical simulation has been conducted to investigate the effects of the geometry and the installation of the inlet nozzle on the aerodynamic and acoustic performance of a small squirrel-cage fan. Both the eccentric inlet nozzle and the elliptical inlet nozzle with different levels of the eccentricity ratio and the attitude angle have been tested to search an optimal assembly to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…They suggested that the design method of the downsized volute profile is more suitable for slight space limitation, while the design method of the partial flow volute profile is more suitable for significant space limitation. Wen indicates that an optimal elliptical inlet nozzle can reduce flow loss before fluid entering into the impeller passages and induce a tip flow pattern, contributing to promote the volume flow rate and suppress the leaking flow loss (Wen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the design method of the downsized volute profile is more suitable for slight space limitation, while the design method of the partial flow volute profile is more suitable for significant space limitation. Wen indicates that an optimal elliptical inlet nozzle can reduce flow loss before fluid entering into the impeller passages and induce a tip flow pattern, contributing to promote the volume flow rate and suppress the leaking flow loss (Wen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In such, the blade inlet angle of many squirrel cage fans is about 80 degrees and the blade inlet angle is about 10 degrees. The total pressure efficiency of most squirrel cage fans can only reach to 45% (Rafael, 2009;Kim and Seo, 2004;Suarez et al 2006;Wen et al 2016;Wen et al 2013). A larger inlet angle not only causes a large airflow impact at the blade inlet, but also makes the airflow difficult to enter the blade passages.…”
Section: Introductionmentioning
confidence: 99%
“…Wen et al. 12 investigated the impact of an elliptical inlet nozzle on the performance of a small squirrel cage fan. Kim et al.…”
Section: Introductionmentioning
confidence: 99%
“…Kim 6 compared several profile schemes and found that fine-tuning the volute profile may not only reduce noise but also improve the performance. Wen et al 7 found that an improper profile can cause a reduction in the total pressure and efficiency. The state of correlation research is yet fragmented and unsystematic, and there is no consensus regarding how the volute profile affects the fans' performance.…”
Section: Introductionmentioning
confidence: 99%